How Do Terrorists Choose Their Targets for an Attack? The View from inside an Independent Cell - Torres-Soriano, Manuel Ricardo (Terrorism and political violence, 2021)
The present article aims to further our understanding of the process whereby terrorists choose targets for attacks. It offers a case study based on information from a jihadist cell broken up by police in the province of Barcelona, Spain in April 2015 in Operation Caronte. Based on detailed analysis of conversations between cell members, obtained thanks to infiltration by an undercover police officer, it argues that the terrorist brainstorming was informed by four main factors: organizational, contextual, logistical, and geographical. The materialization of the desire to use violence in an attack plan was the dynamic outcome of the way these factors modulated the will of the terrorists.